The Influence of Product Quality and Price on Purchase Decisions - Rizky Ferrari Oktavian; Henky Wahyudi (Almana : Jurnal Manajemen dan Bisnis, 2022)
Purchase decisions are actions taken by consumers to buy products by carrying out existing considerations, including how product quality and price. Therefore, both have a significant role in influencing Purchase Decisions. The purpose of this research is to find out how Product Quality, Price, and Purchase decisions are applied by Mixue cafe. And to find out how big the influence of Product Quality on Purchase Decisions, the effect of Price on Purchase Decisions, and the influence of Product Quality and Price on Purchase Decisions. In this study, the sample used was consumers who were respondents in this study as many as 88 people, with questionnaire data collection techniques and multiple linear analysis, to process data using SPSS 21 For Windows and Microsoft Excel programs, the analytical method used was the quantitative method with analysis descriptive and verification. The results of this study state that the product quality is in a good category, the price is in the good enough category, and the purchase decision is in a good category, the results of the T-test indicate that product quality has an effect on the purchasing decision, the price has an effect on the purchase decision, and the F-test shows that Product Quality and Price affect the Purchase Decision.